Mobilidade urbana em Serrinha: transporte alternativo como solu??o - Souza, Ciciane Santos Oliveira (2023)
The analysis of urban mobility in Brazil starting from the municipality of Serrinha values the study of space as territorial planning. Discussions used on alternative transport confirm the importance of discussing mobility in municipalities as a matter of planning, territorial and urban order, without neglecting public management issues. Alternative transport operating on roads and highways is subject to the rigor of legislation, even if they do not comply with regulations.A final product was created in the form of an application, called Serrinha Mob, developed with the aim of assisting the municipality's actions on urban mobility, considering the roads in areas of urban expansion, those that require infrastructure and road planning. Therefore, research in the municipality of Serrinha on urban mobility is being built at a slow pace, being conditioned to await decisions taken by the municipal public authorities. The regulation of alternative transport in Serrinha, based on laws and norms, must comply with the criteria based on the determinations of federal legislation. Serrinha, as a municipality that receives the daily demands of neighboring municipalities, must offer conditions to receive this flow of people and vehicles